Exploration of Constraints and Strategies to Increase Public Interest and Saving Experience in Bank Syariah Indonesia Financial Services: Case Study of Bank Syariah Indonesia in Medan, North Sumatra - Asshifa Nazila Aridzki; Ahmad Syakir; Nursantri Yanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The main objective is to explore the constraints and solutions in increasing public participation in sharia financial services at Bank Syariah Indonesia (BSI), particularly in Medan, North Sumatra. The proposed hypothesis is that sharia financial literacy and effective education can increase public awareness and interest in BSI services. The method used is qualitative with a descriptive approach. Data were collected through structured questionnaires, interviews, observations, and documentation from 115 BSI customers in Medan. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing and verification. The results indicate several main obstacles, namely the low level of sharia financial literacy (only 12.5% of respondents have a strong understanding of sharia financial principles), the limited effectiveness of promotions (50.9% feel the promotions are quite effective, while 23.7% find them less informative), and technical challenges such as difficulties in migrating the application to Beyond (37.5% of respondents) and the instability of the BSI Mobile application (59% of respondents). The recommended strategies include strengthening community-based education programs, collaborating with educational institutions, diversifying promotional media, and investing in technological infrastructure. The importance of financial and technological literacy in enhancing sharia financial inclusion is a key focus, while also providing strategic recommendations for BSI to expand its service reach. The results are expected to serve as a reference for the development of more inclusive marketing strategies and educational programs.